PENGEMBANGAN E-MODUL BERNUANSA GAYA BELAJAR UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS X SMA/MA - Ismirranda, Ayutia (Jurnal Edukasi dan Penelitian Matematika, 2024)
Abstract - This research aims to validate the e-module with learning style nuances to improve the mathematical communication skills of class X SMA/MA students. The method used for this purpose is to use the Plom model. The research subjects were 24 class X students. The data collection methods for this research are questionnaires, documentation and observation. Meanwhile, preliminary research uses data reduction, data presentation, and drawing conclusions and analysis for product validity using a Likert scale. From the research results, the results obtained for the validity of the e-module are 83.79 with valid criteria. With the substance aspect of the material getting a value of 84.67 which is in the valid criteria, the feasibility aspect of presentation gets a validity value of 87.64 which is in the valid criteria, the display feasibility aspect gets a validity value of 83.84 which is in the valid criteria, in terms of language it gets a validity value of 82, 00 with valid criteria and in terms of aspects of the differentiated learning approach and numeracy literacy with a validity value of 80.8 it is within the valid criteria. So, overall the average validity of Prototype 1 e-module from the five validators was obtained. Based on this explanation, the e-module with learning style nuances to improve the mathematical communication skills of class X SMA/MA students is valid.Keywords– e-module, mathematical communication skills, nuances of learning styles